2015
DOI: 10.1371/journal.pone.0128330
|View full text |Cite
|
Sign up to set email alerts
|

Superovulation Using the Combined Administration of Inhibin Antiserum and Equine Chorionic Gonadotropin Increases the Number of Ovulated Oocytes in C57BL/6 Female Mice

Abstract: Superovulation is a reproductive technique generally used to produce genetically engineered mice. Superovulation in mice involves the administration of equine chorionic gonadotropin (eCG) to promote follicle growth and then that of human chorionic gonadotropin (hCG) to induce ovulation. Previously, some published studies reported that inhibin antiserum (IAS) increased the number of ovulated oocytes in ddY and wild-derived strains of mice. However, the effect of IAS on the C57BL/6 strain, which is the most wide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 109 publications
(86 citation statements)
references
References 32 publications
1
81
0
4
Order By: Relevance
“…The mice were genotyped by manufacturer’s recommendation with the following primer sets; FW 5′-CTTCCAAGAGTTCAACTACCG-3′ and RV 5′-TCTACCAGCTCAGCCACAGTG-3′ (245 bp). In some experiments, reproductive techniques established by Center for Animal Resources and Development (CARD) were applied to efficiently produce an optimal number of mice with stably exhibiting pulmonary phenotypes61. The mice were housed in a vivarium in accordance with the guidelines of the animal facility center of Kumamoto University and were fed with normal chow ad libitum .…”
Section: Methodsmentioning
confidence: 99%
“…The mice were genotyped by manufacturer’s recommendation with the following primer sets; FW 5′-CTTCCAAGAGTTCAACTACCG-3′ and RV 5′-TCTACCAGCTCAGCCACAGTG-3′ (245 bp). In some experiments, reproductive techniques established by Center for Animal Resources and Development (CARD) were applied to efficiently produce an optimal number of mice with stably exhibiting pulmonary phenotypes61. The mice were housed in a vivarium in accordance with the guidelines of the animal facility center of Kumamoto University and were fed with normal chow ad libitum .…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we have developed an ultra-superovulation method to collect more oocytes from female mice compared with conventional superovulation methods (Takeo and Nakagata, 2015), and we demonstrated that zygotes created via ultra-superovulation combined with IVF are also applicable for the production of various GM mice by direct microinjection of genome editing reagents (Nakagawa et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Co-injection of inhibin antiserum and PMS, also termed hyperovulation, is effective in several wild-derived mouse strains and has recently been shown to increase superovulation yields approximately 3-fold in C57BL/6J mice [27]. This method may therefore increase the feasibility of high-speed backcrossing onto a C57BL/6J background and potentially other strains, by providing a larger number of offspring to screen, at the cost of transiently increasing colony size and number of animals involved.…”
Section: Resultsmentioning
confidence: 99%